Computational modeling of anodic current distribution and anode shape change in aluminium reduction cells - Xu Y.; Li J.; Zhang H.; Lai Y. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In aluminium reduction cells, the profile of a new carbon anode changes with time before reaching a steady state shape, since the anode consumption rate, depending on the current density normal to anode surfaces, varies from one region to another. In this paper, a two-dimension model based on Laplace equation and Tafel equation was built up to calculate the secondary current distribution, and the shift of anode shape with time was simulated with arbitrary Lagrangian-Eulerian method. The time it takes to reach the steady shape for the anode increases with the enlargement of the width of the channels between the anodes or between the anode and the sidewall. This time can be shortened by making a sloped bottom or cutting off the lower corners of the new anode. Forming two slots in the bottom surface increases the anodic current density at the underside of the anode, but leads to the enlargement of the current at the side of the anode.